UNDERSTANDING INDO-PACIFIC: A FOCUS ON THEORETICAL CONTEXT - Joyprokash Mondal (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to examine whether traders in Ujung Berung Market carry out buying and selling activities in accordance with the hadith of Islamic business ethics, which include honesty, trustworthiness, fairness, not selling prohibited goods, not swearing falsely, and not committing najasy (fraud) acts. This study uses a qualitative method with a descriptive approach, collecting data through interviews, observations, and documentation involving 25 traders, 3 buyers, and 2 market administrators as samples from a total of 250 traders. The results of the study indicate that most traders in Ujung Berung Market understand the principles of Islamic business ethics, although some only know the basics. Although there are traders who have never violated, there are also traders who still carry out buying and selling practices that are contrary to the hadith of business ethics. In conclusion, traders in this market generally know the hadith of Islamic business ethics, although their understanding is often limited to the basics, and there are still buying and selling practices that are not in accordance with the hadith. Keywords: Business ethics, Hadith science, Buying and selling, Hadith business ethics, Living hadith